2013
DOI: 10.3390/s130302848
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Low-Cost Sensor Prototype for Monitoring Temperature during Wine Fermentation in Tanks

Abstract: This paper presents a multipurpose and low cost sensor for temperature control over the wine fermentation process, in order to steadily communicate data through wireless modules in real time to a viticulturist's mobile or fixed device. The advantage of our prototype is due to the fact that it will be used by small winemakers in the “Ribera del Duero” area, and as it is a cheaper sensor and easy to use for the control and monitoring of the grape fermentation process, it will probably be used by other business m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 17 publications
(11 reference statements)
0
12
0
Order By: Relevance
“…The literature on automatic systems for controlling fermentation based on wireless sensors is mostly focused on wine. Among them, Ranasinghe et al (2013) propose measuring the temperature gradient across a fermentation tank with a sensor array constructed to accommodate seven wireless resistance temperature detectors capable of real-time monitoring of fermentation vats, while Di Gennaro et al and Sainz et al (Di Gennaro et al 2013;Sainz et al 2013) focus on wireless sensor communication issues.…”
Section: Introductionmentioning
confidence: 99%
“…The literature on automatic systems for controlling fermentation based on wireless sensors is mostly focused on wine. Among them, Ranasinghe et al (2013) propose measuring the temperature gradient across a fermentation tank with a sensor array constructed to accommodate seven wireless resistance temperature detectors capable of real-time monitoring of fermentation vats, while Di Gennaro et al and Sainz et al (Di Gennaro et al 2013;Sainz et al 2013) focus on wireless sensor communication issues.…”
Section: Introductionmentioning
confidence: 99%
“…Such modules suffer from several drawbacks including that the usual transmission range for bluetooth devices is only a few meters which makes the monitoring system unsuitable for practical use in large wineries where the barrels are constantly being moved around, whilst the accuracy of the analogue temperature sensor would not be as good if a digital temperature was used [14]. Consequently, it appeared to us that our system, which employs a Moteino microcontrollor with an integrated low power FM radio as the sensor platform and main network interface along with a digital temperature probe, will offer additional advantages over what has thus far been reported.…”
Section: The Overall Systems Architecturementioning
confidence: 99%
“…In terms of vineyard monitoring, several reports have appeared recently detailing the use of WSN to monitor not only a vineyard’s microclimate but also the risk of vine damage due to frost, pests and disease [10,11,12]. There have also been several reports utilising WSN to monitor the quality of wine in terms of cellaring [13], and temperature control at the various stages of vinification [14,15]. Controlling the temperature during primary fermentations of wine is extremely important in terms of the development of the “bouquet” or “aroma” of a wine.…”
Section: Introductionmentioning
confidence: 99%
“…In the last years, WSNs have been widely used for different monitoring solutions both in the vineyard [12][13][14][15] and cellar [1][2][3][4][5]16]. As reported by Jones and Davis [17], temperature is a critical factor to control during alcoholic fermentation, but different stages of the winemaking process require the monitoring of many other parameters.…”
Section: Conclusion/outlookmentioning
confidence: 99%
“…While large wineries frequently utilize steel fermenting vats equipped with temperature sensors, the smaller ones generally perform temperature measurements manually to reduce the costs of deploying wired sensors and actuation infrastructure. Many authors have suggested low-cost solutions to this using wireless temperature monitoring systems [1][2][3][4]. However, a correct winemaking monitoring needs to control many other processes and consequently many other parameters in addition to temperature.…”
Section: Introductionmentioning
confidence: 99%